Development and Evaluation of Mycelium-Based Composites from Agroforestry Residues: A Sustainable Approach to the Design of Innovative Building Materials - Consuelo Fritz; Juan Francisco Olivera; Víctor Garrido-Manque; Rosemarie Garay (Buildings)
This study explored mycelium-based composites (MBCs) as a sustainable alternative to conventional materials, focusing on the role of lignocellulosic substrates in optimizing their physical, mechanical, and biodegradability properties. It also addressed the valorization of agroforestry by-products, particularly European hazelnut shells (HZ) and radiata pine sawdust (SW), in an effort to reduce waste and minimize environmental impacts. The MBCs were obtained using two formulations (HZ100 and HZ75-SW25) of local agroforestry by-products bound together with natural growth of fungal mycelium from Ganoderma sp. We examined the physical and mechanical properties of these novel materials, including the density, shrinkage, water absorption, hydrophobicity, moduli of rupture and elasticity, and internal bond strength. Additionally, we assessed the biodegradability of the MBCs in soil to estimate the time required for complete degradation. The results clearly indicated differences in performance between the MBCs from HZ100 and HZ75-SW25. In general, HZ75-SW25 demonstrated superior mechanical performance compared to HZ100. Water absorption was low in both cases, suggesting a degree of hydrophobicity on the surface. The biodegradation results indicated that the fabricated MBCs could fully decompose in less than one year when buried in soil, confirming that these biocomposites are entirely biodegradable.